ISG15 Enhances the Activity of γ‐Glutamate Cysteine Ligase to Suppress Apoptosis in High Fat Diet‐Promoted Hepatocellular Carcinoma - Xinran Liu; Qiujin Ma; Zhao Jia; Yihao Zhou; Churong Zou; Yushuo Xiao; Yuchen Chen; Chuyao Ma; Liangliang Song; Jing Yang; Chen Wang; Huidie Xu; et al. (Advanced Science)
Abstract Obesity is a leading risk factor for development of hepatocellular carcinoma (HCC). High‐fat intake produces cytotoxic effects in liver cells, such as excessive reactive oxygen species (ROS) accumulation and apoptosis. How HCC cells regulate ROS level and escape the cytotoxic effects of high fat diet (HFD) stress remains unclear. Herein, this work reports a critical anti‐ROS/apoptotic role of the ubiquitin‐like protein interferon stimulated gene 15 (ISG15) in HFD‐promoted HCC. In mouse models and clinical HCC samples, upregulation of ISG15 is associated with hepatic steatosis. Notably, upregulated ISG15 elevates cellular glutathione levels, which subsequently reduces ROS accumulation and confers resistance to apoptosis in HCC cells. In diethylnitrosamine‐induced HCC mouse model, HFD‐feeding promotes HCC progression in wildtype mice, while tumor growth is significantly suppressed accompanied by apoptosis of HCC cells in Isg15‐KO mice. Mechanistically, ISG15 promotes the activity of γ‐glutamate cysteine ligase (γ‐GCL), a rate‐limiting heterodimeric holoenzyme of glutathione synthesis consisting of glutamate‐cysteine ligase catalytic subunit (GCLC) and glutamate‐cysteine ligase modifier subunit (GCLM). Independent of ISGylation, ISG15 forms an ISG15/GCLM/GCLC complex that promotes GCLM‐GCLC interaction, increases glutathione generation and inhibits HFD‐induced apoptosis in HCC cells. Together, an anti‐apoptotic ISG15‐γ‐GCL‐glutothione axis is suggested in HFD‐promoted HCC.